A First-Principles Study of Gas Molecule Adsorption on Carbon-, Nitrogen-, and Oxygen-Doped Two-Dimensional Borophene. (20th December 2021) - Qin, Xinmao; Yan, Wanjun; Li, Dongxiang; Zhang, Zhongzheng; Chen, Shaobo
Abstract : A first-principles study was performed to investigate the adsorption properties of gas molecules (CO, CO2, NO, and NO2 ) on carbon- (C-), nitrogen- (N-), and oxygen-doped (O) borophene. The adsorption energies, adsorption configurations, Mulliken charge population, surface work functions, and density of states (DOS) of the most stable doped borophene/gas-molecule configurations were calculated, and the interaction mechanisms between the gas molecules and the doped borophene were further analyzed. The results indicated that most of the gas molecules exhibited strong chemisorption at the VB site (the center of valley bottom B–B bond) of the doped borophene (compared to pristine borophene). Electronic property analysis of the C-doped borophene/CO2 and the NO2 adsorption system revealed that there were numerous charge transfers from the C-doped borophene to the CO2 and NO2 molecules. This indicated that C-doped borophene was an electron donor, and the CO2 and NO2 molecules served as electron acceptors. In contrast to variations in the adsorption energies, electronic properties, and surface work functions of the different gas, C-, N-, and O-doped borophene adsorption systems, we concluded that the C-, N-, and O-doped borophene materials will improve the sensitivity of CO, CO2, and NO2 molecule; this improvement of adsorption properties indicated that C-, N-, and O-doped borophene materials are excellent candidates for surface work functions transistor to detect gas molecules.